2014
DOI: 10.1039/c4ra03560g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine PEG-capped gadolinia nanoparticles: cytotoxicity and potential biomedical applications for MRI and luminescent imaging

Abstract: Ultrafine PEG-capped gadolinium oxide NPs doped with erbium ions, which could serve as a dual-imaging agent for MRI/optical imaging were synthesized using a simple, green, and quick method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…4. In the IR spec- trum of sample (a), PEG has characteristic vibration bands at 3458 cm À1 corresponding to the ʋ as AOAH stretching band, at 2875, 1342, and 950 cm À1 corresponding to ʋACAH stretching and dACAH bending bands, respectively, and at 1104 cm À1 corresponding to the ʋACAOAC stretching band [12,22,29]. After the thermal decomposition process, three additional vibration bands appeared at around 1542, 1436, and 540 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4. In the IR spec- trum of sample (a), PEG has characteristic vibration bands at 3458 cm À1 corresponding to the ʋ as AOAH stretching band, at 2875, 1342, and 950 cm À1 corresponding to ʋACAH stretching and dACAH bending bands, respectively, and at 1104 cm À1 corresponding to the ʋACAOAC stretching band [12,22,29]. After the thermal decomposition process, three additional vibration bands appeared at around 1542, 1436, and 540 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…The paramagnetic character of these Gd 2 O 3 @PEG nanoparticles is commonly shared by positive contrast agents for magnetic resonance imaging (MRI) [48,49]. The slope of the M-H curve corresponds to a susceptibility, j, of 8.2 Â 10 À5 which is greater than the susceptibility of PEG-coated Gd 2 O 3 :Er 3+ nanoparticles (j = 2.0 Â 10 À5 ) [29]. However, Huang et al [34] who studied magnetic characteristics of hollow Gd 2 O 3 particles, reported that paramagnetism of the particle species turned superparamagnetic in the present of carbon residue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spherical Gd 2 O 3 NPs were fabricated according to the reported protocols [7,10]. First, a sealed beaker with a freshly prepared aqueous solution of gadolinium nitrate (0.001 mol in 40 mL of H 2 O) was placed into an electrical furnace and heated to 90 ℃ for 1.5 h. The dried precipitates were then calcined in air at 800 ℃ for 1 h to produce the gadolinia particles.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The higher density of magnetic ions is the main advantage of using paramagnetic gadolinium oxide NPs as a "positive" CA [6]. The resulting gadolinia NPs covered with biocompatible polyethylene glycol (PEG) have been used in cell labeling studies [6,7]. In particular, thin PEG layer on the surface of Gd 2 O 3 enhances the steric repulsion between NPs, and prevents protein adhesion that leads no NPs aggregation [8].…”
Section: Introductionmentioning
confidence: 99%